Effectiveness of a Brief Intervention Using Genetic Polymorphism of Alcohol-Metabolizing Enzymes on Excessive Drinking among Japanese College Students and Young Adults: A Randomized Controlled Trial - Owaki, Yukiko (Disease and Health Research: New Insights Vol. 4, 2024)
Background: This open-label, randomized controlled trial evaluated the effect of a brief intervention considering five genotype combinations of enzymes involved in alcohol metabolism (ALDH2 and ADH1B) in the students and staff of a university aged 20–30 years who were excessive drinking behavior (average amount of alcohol consumed, men: \(\ge\)4 drinks/per day and women: \(\ge\)2 drinks/per day; 1 drink = 10 g of pure alcohol equivalent). Methods: Focusing on the primary endpoint “average daily alcohol consumption” (g pure alcohol equivalent), data were collected from a randomized self-administered questionnaire survey linked by ID number and six-month drinking records, with both the intervention and control groups surveyed at 1, 3, and 6 months after intervention and from baseline, respectively. The intervention group was genotyped for alcohol-metabolizing enzymes using saliva, and recorded the amount and contents of alcohol consumed on drinking days until the results were reported approximately one month later, and after the results were reported, the intervention was conducted in person or online for 30 minutes. The control group received traditional materials, and genetic testing was conducted at 6 months (at the end of the study) on a voluntary basis. The Wilcoxon signed rank test was used for pre- and post-intervention comparisons, and the Mann–Whitney U test was used for between group comparisons at baseline and at 1, 3, and 6 months. Results: By the end of June 2023, 204 participants had registered and were allocated into the intervention (n=100) and control (n=96) groups using simple randomization. The mean age was 22.5 years (85 men; 111 women). Average daily alcohol consumption decreased significantly in the intervention group between “baseline to 1 month” and at 1, 3, and 6 months after the intervention (p<0.01). No significant difference was observed in the control group at all time points. Furthermore, no significant difference was found between the groups at baseline, after which the intervention group consumed significantly less average alcohol at 3 months after the intervention (p<0.01). Conclusion: Average daily alcohol consumption significantly reduced in the intervention group at 6 months. Genetic testing for alcohol-metabolizing enzymes and health guidance on type-specific excessive drinking may be useful in reducing sustained average alcohol consumption.